A mathematical model of swimming performance improvement for goal setting and program evaluation - McClements, J. D.; Laverty, W. H. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
This study was done to develop a mathematical model to be used to measure objectively performance improvement in swimming. The basis of this analysis was developmental change over a 12-year period. Performance improvement is the basic goal of all coaches, athletes, and sport administrators. Setting goals and evaluating performance improvement have been based on relative comparisons with peer athletes or "personal bests." The basic question is, "how much improvement is meaningful?" Research on goal setting and self-directed behavior change by Kolb and Boyatzis (1970) concluded that the goal-setting process is crucial for success. A mathematical model of improvement should make this process more objective.